Glycaemic control improves fibrin network characteristics in type 2 diabetes – A purified fibrinogen model - Pieters, Marlien; Covic, Namukolo; van der Westhuizen, Francois H.; Nagaswami, Chandrasekaran; Baras, Yelena; Loots, Du Toit; Jerling, Johann C.; Elgar, Dale; Edmondson, Kathryn S.; van Zyl, Danie G.; Rheeder, Paul; Weisel, John W. (Thrombosis and Haemostasis, 2008)
Diabetic subjects have been shown to have altered fibrin network structures. One proposed mechanism for this is non-enzymatic glycation of fibrinogen due to high blood glucose. We investigated whether glycaemic control would result in altered fibrin network structures due to decreased fibrinogen glycation. Twenty uncontrolled type 2 diabetic subjects were treated with insulin in order to achieve glycaemic control. Twenty age- and body mass index (BMI)-matched non-diabetic subjects were included as a reference group. Purified fibrinogen, isolated from plasma samples was used for analysis. There was a significant decrease in fibrinogen glycation (6.81 to 5.02 mol glucose/mol fibrinogen) with a corresponding decrease in rate of lateral aggregation (5.86 to 4.62) and increased permeability (2.45 to 2.85 × 10−8 cm2) and lysis rate (3.08 to 3.27 μm/min) in the diabetic subjects after glycaemic control. These variables correlated with markers of glycaemic control. Fibrin clots of non-diabetic subjects had a significantly higher ratio of inelastic to elastic deformation than the diabetic subjects (0.10 vs. 0.09). Although there was no difference in median fiber diameter between diabetic and non-diabetic subjects, there was a small increase in the proportion of thicker fibers in the diabetic samples after glycaemic control. Results from SDS-PAGE indicated no detectable difference in factor XIIIa-crosslinking of fibrin clots between uncontrolled and controlled diabetic samples. Diabetic subjects may have altered fibrin network formation kinetics which contributes to decreased pore size and lysis rate of fibrin clots. Achievement of glycaemic control and decreased fibrinogen glycation level improves permeability and lysis rates in a purified fibrinogen model
Keywords: Diabetes; fibrin network; fibrinogen glycation; glycaemic control; hyperglycaemia